2020
DOI: 10.3390/su12072587
|View full text |Cite
|
Sign up to set email alerts
|

Does the Mixed-Ownership Reform Affect the Innovation Strategy Choices of Chinese State-Owned Enterprises?

Abstract: In recent years, the innovation of state-owned listed enterprises has gained substantial momentum in academic research due to their vital role in sustainable economic development. This article examines and evaluates the influence of mixed-ownership reform on the innovation strategy of Chinese State-Owned Enterprises (SOEs) from the two dimensions of ownership structure adjustment and control right allocation. We extend extant research in that: The diversity of mixed shareholders, the depth of mixed equity, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…By following the common practices of the existing literature and the intensity of innovation investment R&D is used to proxy innovation motivation [ 27 – 29 ]. R&D is specifically defined as the ratio of the company’s annual R&D expenditure to the total assets at the beginning of the year [ 27 , 30 – 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…By following the common practices of the existing literature and the intensity of innovation investment R&D is used to proxy innovation motivation [ 27 – 29 ]. R&D is specifically defined as the ratio of the company’s annual R&D expenditure to the total assets at the beginning of the year [ 27 , 30 – 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Privatization may in fact allow the adoption of a more aggressive and stimulating structure of incentives for managers (Hart, Shleifer, & Vishny, 1997). Private shareholders can bring a more mature management experience and technical know‐how to the company, support the entrepreneurship of executives, provide more opportunities for market competition, and improve the operating efficiency and sustainability of MOCs (Li, Yuan, Khan, Pervaiz, & Sun, 2020). Private firms may exploit scale economies through the coverage of several territorial jurisdictions.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The majority of studies argue that the private sector is more efficient than the public one, apart from the existence of some incentive losses over time (Dijkgraaf & Gradus, 2007; Szymanski & Wilkins, 1993), a small number of studies found public waste utility companies being more efficient than private ones, whereas a good number of them did not find any significant differences. As there is growing trend towards the adoption of private management techniques in such companies, the public versus private management issue has become a highly relevant topic in literature (Bel, Hebdon, & Warner, 2007; Bel & Warner, 2015; Li et al, 2020). Many studies have been carried out, often associated with divergent conclusions depending on the sample and on the technique chosen.…”
Section: A Research Note From An Italian Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, as the world’s largest emerging economy and the leading destination of foreign direct investment [ 42 ], China is in an emerging economy with the most rapid economic and technological development, and plays an important role in the international strategies of many multi-national corporations [ 43 45 ], so we select Chinese listed companies as our empirical database, we collect the information of 185 companies during the year 2012 to 2017 as our dataset, we chose this sample as empirical dataset because these enterprises have fewer missing values in the selected years, and they also have more overseas R&D activities and domestic R&D activities, the selection of these enterprises can maintain the integrity and authenticity of our data and maximize the sample size. Specifically, this is the final sample that we had passed through layers of criteria and screening in the database.…”
Section: Introductionmentioning
confidence: 99%